Sodium Stearoyl-2 Lactylate Production from Lactic Acid and Stearic Acid for Emulsifier - Lindawaty
Emulsifiers as food additives are commonly added to processed foods to maintain food shape and to stabilize an emulsion system. One of emulsifiers that is often used in bread is sodium stearoyl-2 lactylate (SSL). SSL is an emulsifier derived from the reaction of lactic acid and stearic acid, followed by addition of sodium hydroxyde. This research aims to determine how temperature, mole ratio, time of reaction, and water vapour elimination affect SSL production. The composition of lactic acid, stearic acid, and sodium hydroxyde (2.2:1:1; 2.4:1:1; 2.6:1:1), the temperature (140-200°C), and reaction time (3-5 hours) of SSL production were varied. Parameters that were analyzed to examine the quality of SSL produced are acid value, saponification value, reaction conversion, and color of SSL. The result shows that the acid and saponification values are inversely proportional to the increase in temperature and time. Additionally, acid and saponification values of the product taken in the reaction with mole ratio of 2,6:1:1 (lactic acid: stearic acid: sodium hydroxide) at 180°C for 5 hours have the lowest acid value (150,96 mg KOH/g) and saponification value (246,41 mg KOH/g). The conversion is inversely proportional to the increase in acid value. SSL production is a first order reaction thus mole ratio should affect reaction rate. Reaction constant of SSL production increases as the temperature increases, thus the reaction rate increases as the temperature increases. The conversion is ranged between 60,59%-67,79%. Water vapour elimination was also carried out in this study by adding a vacuum pump to the reaction system. This results in reduced acid and saponification values to 111,55 mg KOH/g and 203,19 mg KOH/g, so that the mentioned values could correspond with the specification value stated in Commision Regulation (EU) No 231/2012. Product colour analysis shows that as the temperature increases, the product obtained has a bigger total colour difference.